1991
DOI: 10.1073/pnas.88.6.2278
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms associated with the generation of biologically active human immunodeficiency virus type 1 particles from defective proviruses.

Abstract: The human immunodeficiency virus (HIV) is the etiological agent of acquired immunodeficiency syndrome (AIDS). HIV exhibits extensive genetic diversity and it is apparent that an infected individual contains different populations of distinct viral strains, a large proportion of which has been found surprisingly to be defective for replication. A similar phenomenon has also been observed with some cell lines that are known to produce infectious viral particles but harbor defective proviral genomes. Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…A chronic HIV-1 producer cell line A1953 [45] was pretreated for 24 h using 100 and 1,000 nM GSK002, 100 and 1,000 nM GSK1264, or diluent control (DMSO). The cells were washed with 1 x PBS and incubated with fresh medium containing inhibitor or DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…A chronic HIV-1 producer cell line A1953 [45] was pretreated for 24 h using 100 and 1,000 nM GSK002, 100 and 1,000 nM GSK1264, or diluent control (DMSO). The cells were washed with 1 x PBS and incubated with fresh medium containing inhibitor or DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…The continuous evolution of HIV, deemed useful for "immunological escape," is sustained by a high rate of mutation and a high rate of replication. The high mutation rate is driven by the error-prone process of reverse transcription (5)(6)(7)63) and by recombination (34,35,94). The end result is the generation of the large range of viral diversity and a predominance of defective virus.…”
Section: Defective Virus Preferentially Drives the Mhc Class II (Cd4 mentioning
confidence: 99%
“…For example, it has been reported that most infected spleen cells in vivo have 11 HIV copy; a single cell can contain up to seven different copies of HIV-1 DNA [11]. It has also been shown that cells harboring 5 copies of defective provirus were able to produce highly infectious viral progeny [12].…”
mentioning
confidence: 98%